An unusual cause of paediatric abdominal pain: Mesenteric masses accompanied with volvulus - Yang, Chao; Wang, Shan; Zhang, Jun; Kong, Xiang-Ru; Zhao, Zhenzhen; Li, Chang-Chun (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Volvulus caused by mesenteric masses is rare and may result in serious consequences. This study aimed to better characterize volvulus caused by mesenteric masses in children. Materials and Methods: A retrospective study was conducted in 24 patients who underwent surgical treatment between January 1994 and January 2014 in one single institution. Results: There were 10 boys and 14 girls. The most frequent findings were abdominal pain (100%), emesis (91.7%) and nausea (83.3%). Physical examination showed positive ileus signs in majority cases, and palpable mass was found in half of the patients. Ultrasound and CT scans revealed mesenteric masses in 21 and 24 patients, and ‘whirlpool sign’ was observed in 19 and 22 patients, respectively. Emergency laparotomy was performed in all patients. Histological examination revealed that 18 cystic masses were lymphangioma, 5 solid cases were lipoma and the remaining one was lipoblastoma. The postoperative course was uneventful in 22 patients, and postoperative obstruction and incision infection occurred in 2 patients. There was no evidence of recurrence at follow-up. Conclusion: Volvulus caused by mesenteric masses is a rare but potentially life-threatening cause of abdominal pain, which should be considered in the differential diagnosis of paediatric acute abdominal pain.